Getting to Now: Entrepreneurial Business Model Design and Development - Masaro, Matthew (Université d'Ottawa / University of Ottawa, 2016)
The purpose of this thesis is to uncover and examine the processes that start-up entrepreneurs go through while designing and then developing their business models. This is done with the intent of deciphering the kind of development that might ultimately lead to a unique or innovative business model. This study uses primary qualitative data generated from interviews with founding entrepreneurs and managers who still participate in running the organization. Each of these organizations participates in the men’s retail market. The research design and methodology of this research uses a grounded-theory coding procedure to analyze the data. Three questions guide this research forward and the findings are threefold. First, for these organizations two business model design paths were followed, herein referred to as the path to ‘Alleviate Pain’ and as the path to ‘Adopt and Modify.’ Second, entrepreneurial leaders tended to act as arbiters when developing their business models, mediating between the set of information accrued during operations and three identified factors. Thirdly, new research into whether or not business model innovations are the result of ex-ante insights or ex-post operational learning is presented. And the findings tend to indicate that both ex-ante insights and ex-post learning are important, but their importance is temporally induced. Lastly, a brief discussion is carried out on how this research informs the entrepreneurial business model creation process (see entrepreneurial practicum) and how it adds to the current literature on business models and business model innovation.
Keywords: Business Model(s); Business Model Innovation; Entrepreneurship; Entrepreneurial Strategy; Business Model Design; Business Model Development; Strategy; Retail; Men's Retail; Retail Business Models